Studies in law, politics and society. Vol. 33 - Sarat, Austin; Ewick, Patricia (Elsevier, 2004)
This volume of "Studies in Law, Politics, and Society" presents a diverse array of articles by an interdisciplinary group of scholars. Their work spans the social sciences, humanities, and law. These scholars examine law and culture, the complex intersections of law and policy, and the place of religious values in legal life. The articles published here exemplify the exciting and innovative work now being done in interdisciplinary legal scholarship.